Implementasi Metode Blackbox Testing Dalam Pengujian Fungsionalitas Website Dimsum Gemoy - Mukhlisin, Ahmad Nur; Urdatun Nafi`ah, Anisa; Saifudin, Andoko; Syafiq, Aisy Syarah; Hakim, Ahmad Luqman; Thoib, Imam (STMIK Amika Soppeng, 2025)
The current development of information technology has increased the need for good and high-quality web systems. One important step to ensure software quality is to conduct testing using the black box testing method. This method focuses on system functions without the need to know the internal components. This study aims to test the functionality of the Dimsum Gemoy website using the black box testing method on several main modules, namely the Login, Register, Send Message, Add Item to Cart, Cart Features, and Order Details modules. The total number of tests conducted was 120 test cases, with the results of 50 test cases being successful and 70 test cases failing. The highest success rate was in the Add Item to Cart module at 66.67%, while the lowest was in the Order module at 25.53%. Overall, the test success rate reached 41.67%. These results indicate that the Dimsum Gemoy website still needs improvement, especially in the Send Message and Order Details modules, to run well and provide a more satisfying user experience.